Formation of a Strandline during the 1984 Jökulhlaup of Strandline Lake - Sturm, Matthew (ARCTIC, 1986)
Strandlines, diagnostic features of glacier-dammed lakes, may not always represent highwater markers. They can apparently be formed during jökulhlaups. An example of the formation of a strandline during the 1984 draining of Strandline Lake is given.Key words: strandline, terracette, jökulhlaup, ice-dammed lake, Alaska Mots clés: ligne de rivage, terrassette, débâcle glaciaire, lac contenu par des glaciers, Alaska